Nutrients and trace elements content of wood decay fungi isolated from oak (Quercus ilex). - Campos, Juan a (Biological trace element research, 2011)
The presence of chemical elements and the differences in their concentration in the fruiting bodies of wood decay fungi may reflect their activity either as saprobes or parasites and the intimate physiological relation with the substrate from which they extract their nutrients. In order to test this hypothesis, we carried out a systematic sampling of eight species of wood decay fungi on oak (Quercus ilex). The data show that the concentration of some elements exhibits a very wide range of values for the species tested, which could mean that the relative content of some elements may provide clues about the nature of the substrate and, moreover, about the nutritional physiology. The comparison between the foliar analysis (FA) and the elemental content of fungi may shed light on the specific physiological behaviour of the species. Potassium is an element accumulated in fungal biomass in higher quantities than in the FA. By contrast, calcium appears in foliar analysis in much higher quantities than in fungal fruiting bodies' biomass. Concerning this element, we have also found profound differences between the two species phylogenetic groups and lifestyle. Of all elements measured, we believe that the relative accumulation of K and Ca may be related to the close connection between fungi and the substrate on which they live and may also explain their physiological role as saprobes or parasites. When the lifestyle and the systematic position of the different species sampled were compared, differences also emerged in the content of Na and Ca.
The following values have no corresponding Zotero field: accession-num: 21748305
Keywords: Epiphytic fungi; Heavy metals; Nutrients; Nutrition physiology; Saprobe fungi; Trace Elements